OUTBREAK OF DENGUE FEVER IN LAHORE: STUDY OF RISK FACTORS - Mukhtar, Fatima; Salim, Mohammad; Farooq, Arsalan (Journal of Ayub Medical College Abbottabad, 2012)
Background: Dengue fever is a rapidly emerging arthropod born viral disease threatening to become an international public health problem. Approximately 500,000 people suffer from dengue haemorrhagic fever and dengue shock syndrome with 20,000 deaths annually. Objective of this study was to look into the risk factors associated with the development of dengue fever. Methods: This crosssectional descriptive study was conducted on patients admitted in various hospitals of Lahore with suspected Dengue fever. Data was collected on a questionnaire from 109 conveniently selected patients. Results: Mean age of the patients was 34±16.5 years, and majority (80, 73.4%) were male. Seropositivity for dengue was found in 78 (71.5%). The study did not find significant statistical association of seropositivity with demographic variables. However, source of water supply was found associated with dengue seropositivity (p=0.002). Conclusion: Source of water is a determinant of contracting dengue fever owing to it a breeding media for mosquitoes. All other phenomena associated with use of water and sanitation needs to be part of long term control of dengue that will also contribute to controlling other diseases with the same determinants. Keywords: Dengue fever, dengue haemorrhagic fever, dengue shock syndrome, water sources, epidemic